JAMALUDDIN AL-AFGHANI’S THOUGHTS IN SAREKAT ISLAM AND MUHAMMADIYAH MOVEMENT EARLY 20TH CENTURY - Mahardika, Moch. Dimas Galuh (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
The global political struggle between Muslims and Western imperialists produced new Islamic thinkers. One of them was Jamaluddin Al-Afghani, a pioneer of pan-Islamism whose ideas spread to different parts of the world. His idea of ??political independence for Muslims became the compass for the figures of the early 20th-century movement in the Dutch East Indies, which carried out a movement against colonialism-imperialism. Some major organizations inspired by Jamaluddin Al-Afghani's thoughts are Sarekat Islam and Muhammadiyah. Both organisations play an important role in the machinery of the national movement. Written based on a literature study with a historical approach, the article attempts to explain the influence of Jamaluddin Al-Afghani's thoughts on the political dynamics of Islamic groups during the nationalist movement of the early 20th century.